2009
DOI: 10.1103/physrevc.80.011601
|View full text |Cite
|
Sign up to set email alerts
|

Isospin effects on light charged particles as probes of nuclear dissipation

Abstract: The multiplicities of postsaddle protons and α particles of the heavy systems 234 Cf, 240 Cf, 246 Cf, and 240 U as functions of the postsaddle dissipation strength are calculated in the framework of a dynamical Langevin model coupled with a statistical decay model. It is found that with increasing isospin of the Cf system, the sensitivity of the postsaddle proton and α-particle multiplicity to the dissipation strength decreases substantially, and it disappears for the 240 U system. We suggest that on the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…It was found that the K degree of freedom not only increases fission barrier height, as reported before [19,77], but also changes the stiffness of the nucleus with respect to mass asymmetry coordinate d 2 F /dη 2 The wide set of experimental data available for the reactions 16 O + 208 Pb → 224 Th and 16 O + 232 Th → 248 Cf has been analyzed using the new 4D dynamical model. The prescission neutron multiplicities, fission fragment MED parameters, and anisotropy of angular distribution could be reasonably reproduced for heavy nuclei with the dissipation coefficients k s 0.25 and γ K 0.077 (MeV zs) −1/2 in contrast with 3D calculations [23,24], where a self-consistent description of all observables with the same k s value was impossible for heavy nuclei.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It was found that the K degree of freedom not only increases fission barrier height, as reported before [19,77], but also changes the stiffness of the nucleus with respect to mass asymmetry coordinate d 2 F /dη 2 The wide set of experimental data available for the reactions 16 O + 208 Pb → 224 Th and 16 O + 232 Th → 248 Cf has been analyzed using the new 4D dynamical model. The prescission neutron multiplicities, fission fragment MED parameters, and anisotropy of angular distribution could be reasonably reproduced for heavy nuclei with the dissipation coefficients k s 0.25 and γ K 0.077 (MeV zs) −1/2 in contrast with 3D calculations [23,24], where a self-consistent description of all observables with the same k s value was impossible for heavy nuclei.…”
Section: Discussionmentioning
confidence: 91%
“…(1) and (2), c denotes the elongation parameter, the parameter h describes the variation in the thickness of the neck for a given elongation of the nucleus, and the the mass asymmetry parameter α determines the ratio of the nascent fission fragments volumes.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the deuteron-induced reactions attracted much attention for application purposes, and the inclusive nucleon production reaction is one of the concerned subjects. Our previous work [16,17] suggested a calculation method describing the deuteron-induced inclusive reaction with the CDCC method for the EB process, the Glauber model for the STR process, and the conventional statistical Hauser-Feshbach theory and the two-component exciton model for the statistical processes. The TALYS code [18] was used to calculate the statistical processes.…”
mentioning
confidence: 99%
“…It is however observed [4][5][6] that it is not possible to fit both the n pre and ER data with the same value of η. While a smaller value of η can account for the ER excitation function, a larger value of η is necessary to describe the * Electronic address: santanu@veccal.ernet.in n pre data.…”
mentioning
confidence: 99%